2004
DOI: 10.1073/pnas.0402060101
|View full text |Cite
|
Sign up to set email alerts
|

A role for fast rhythmic bursting neurons in cortical gamma oscillations in vitro

Abstract: Basic cellular and network mechanisms underlying gamma frequency oscillations (30 -80 Hz) have been well characterized in the hippocampus and associated structures. In these regions, gamma rhythms are seen as an emergent property of networks of principal cells and fast-spiking interneurons. In contrast, in the neocortex a number of elegant studies have shown that specific types of principal neuron exist that are capable of generating powerful gamma frequency outputs on the basis of their intrinsic conductances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
153
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(161 citation statements)
references
References 32 publications
7
153
0
1
Order By: Relevance
“…Changes in the amplitude of gamma oscillations may be due to interactions between principal cells and interneurons as the grating patch expands beyond the classical receptive field. These interactions are thought to be mediated by local intrinsic (horizontal) connectivity that might drive gamma oscillations [Cunningham et al, 2004; Whittington et al, 1995] and alter their form and coherence [Jia et al, 2013; Ray and Maunsell, 2010]. …”
Section: Discussionmentioning
confidence: 99%
“…Changes in the amplitude of gamma oscillations may be due to interactions between principal cells and interneurons as the grating patch expands beyond the classical receptive field. These interactions are thought to be mediated by local intrinsic (horizontal) connectivity that might drive gamma oscillations [Cunningham et al, 2004; Whittington et al, 1995] and alter their form and coherence [Jia et al, 2013; Ray and Maunsell, 2010]. …”
Section: Discussionmentioning
confidence: 99%
“…These oscillations are similar to those recorded in vitro in the entorhinal cortex caused by kainate receptor activation [26] , in vitro in the hippocampus caused by cholinergic activation [6,16,27] and in vivo in the hippocampus [5] but are different from the γ oscillations recorded in the CA1 [14,15,28,29] , which showed that both chemically and electrically interconnected interneuronal networks were involved without any contribution from pyramidal cells. The sodium channel blocker, TTX, also largely reduced γ oscillations, suggesting that neuronal action potentials (spikes) contribute to the network oscillations [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrate an in vitro model that shows that a beta2 rhythm (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) can be specifically generated in layer V of neocortex in a manner independent of gamma rhythmogenesis and of glutamatergic synaptic excitation. Beta2 generation in layer V stands in contrast to cortical gamma rhythms that have been shown to originate in layers II͞III in in vitro models (11) and may underlie cortico-cortical synchronization (12).…”
mentioning
confidence: 99%